DINAMIKA BEHAVIORAL FINANCE DI ERA PASCA PANDEMI COVID-19 - Diah Pradnyadewi T; Sudharma, I Wayan Priyana Agus; Jati Primajana, Dewa (Yayasan Nusantara Hasana Berdikari, 2025)
The COVID-19 pandemic has had a significant impact not only on the health sector but also on global economic and financial dynamics. The uncertainty caused by mobility restrictions, government policies, and market fluctuations created high psychological pressure on investors. In this context, Behavioral Finance approaches became increasingly relevant to explain how psychological, social, and emotional factors influence financial decision-making, which cannot be adequately explained by traditional finance theories. During the pandemic, phenomena such as herding behavior, loss aversion, and overconfidence became highly visible, leading to increased market volatility and speculative behavior. Post-pandemic, although social-economic conditions began to recover, the rapid pace of digitalization and the high participation of retail investors in the capital market opened up space for further behavioral changes. This study aims to examine the impact of the pandemic on the dynamics of Behavioral Finance in Indonesia, particularly in the capital market, and how these investor behavior changes will continue to evolve in the post-pandemic era. The research findings are expected to provide insights for regulators, investment managers, and investors to better understand the behavioral biases that occur and formulate more effective strategies in facing market uncertainty in the future.